Effect of different mycobionts on growth parameters of Dactylorhiza hatagirea (D. Don) Soo: implications on conservation strategies - Wani, Abdul Hamid; Qadir, Rukhsana; Bhat, Mohd Yaqub; Dar, Bilal Ahmad (Frontiers in Conservation Science, 2025)
Dactylorhiza hatagirea maintain a symbiotic relationship with rhizospheric fungi in their lifecycle. Rhizospheric fungi have different roles during its growth and development. Although various rhizospheric fungi have been isolated from D. hatagirea, little is known about their specific effects on its growth and development. To understand the role of fungal species on growth parameters of D. hatagirea, we compared the effect of eight fungal species on growth parameters of D. hatagirea. viz. Trichoderma asperellum, Talaromyces falvus, Aspergillus candidus, Circinella muscae, Aspergillus flavus, Aspergillus niger, Cephalosporium acremonium and Trichoderma harzianum in the form of three treatments. Treatment (T1) comprised the combined application of Trichoderma asperellum, Talaromyces falvus, Aspergillus candidus and Circinella muscae. Treatment (T2) comprised the combined application of Aspergillus flavus, Aspergillus niger, Cephalosporium acremonium and Trichoderma harzianum. Another treatment (T3) comprised the combined application of T1 and T2. A separate set of plants which were un-treated with any fungal isolated served as control. Our results revealed that the tubers inoculated with T3 conferred the highest shoot length, tuber length, optimal fresh and dry matter yield, and greatly enhanced other growth parameters, length of inflorescence, number of flowers and specific leaf area. Treatment (T3) has a discernible impact on plant growth compared to the T1, T2 and control. The results revealed that these fungal species we used in the presented study of tested plant D. hatagirea promoted growth with different efficiencies. Our results also revealed that rhizospheric fungal associations with D. hatagirea showed development-dependent preference and hence may provide the basic knowledge for use of different fungal species in conservation of D. hatagirea at different elevations.